Antibacterial and Phytochemical Study of Iraqi Salvia officinalis Leave Extracts - Lana Y. Muttalib; Alaadin M. Naqishbandi (College of Pharmacy University of Baghdad, 2017)
Sage (Salvia officinalis), belong to Labiatae family is indigenous to Iraq and other Mediterranean areas but now cultivated world- wide, principally for its use as culinary herb. In the present study preliminary screening for the important phytochemical natural product groups indicated the presence of flavonoid, saponin, hyrolysable and condensed tannin groups. The antibacterial  activity of two concentrations 10 mg/ml and 100 mg/ml of chloroform and hydroalcoholic extracts from  Salvia officinalis leaves was evaluated against four strains of gram negative bacteria (Escherichia coli,  Pseudomonas arigenossa,  Klebsiella pneumonia, and  Proteus spp) and two strains of gram positive bacteria (Staphylococcus aureus,  Bacillus cerus) using agar well diffusion method. Chloroform extract 100mg/ml was found active against two types of bacteria, Staphylococcus aureus with MIC of 90 mg/ml and Proteus spp with MIC of 80 mg/ml. Bioassay guided separation using TLC led to the separation of 6 constituents from the active extract, one of them was identified as thujone. Key words: Salvia officinalis, Antibacterial, TLC, Thujone.